PAINTING OF THE HANDS AND FEET (Pedagogy of Higher and Secondary Education, 2022)
In the article a role o f value o f this section of on-line tutorial is consideredWb! basic problems which arise up at drawing o f hands and feet are traced.
Keywords: alive nature; big shape; skeleton base; construction